Factors Associated with Klebsiella Bacteremia and Its Outcome in Under-Five Children Admitted with Diarrhea. (29th August 2016) - Akhter, Shamima; Ahmed, Tahmeed; Sarker, Shafiqul Alam; Sarmin, Monira; Shahid, Abu S. M. S. B.; Shahunja, K. M.; Islam, Shoeb Bin; Shahrin, Lubaba; Alam, Tahmina; Alam, Nur Haque; Chisti, Mohammod Jobayer
Abstract : Although Klebsiella bacteremia in children is perceived to be associated with fatal consequences, data are scarce on those children presenting with diarrhea. We evaluated the factors associated with Klebsiella bacteremia in such children. In this retrospective chart analysis, data of all diarrheal children was retrieved from electronic medical record system (named as SHEBA) of Dhaka Hospital of International Centre for Diarrhoeal Disease Research, Bangladesh (icddr, b), from January 1, 2010, to December 31, 2012, who had their blood culture done. This was a study having a case-control design where comparison of clinical and laboratory characteristics was done among children with Klebsiella bacteremia (cases = 30) and those without any bacteraemia (controls = 90). Controls were selected randomly. The cases more often had fatal outcome (p < 0.001 ). In logistic regression analysis, after adjusting for potential confounders such as young age, severe dehydration, severe wasting, abnormal mentation, hypotension, and fast breathing, the cases were independently associated with hospital-acquired infection and positive stool growth (for all, p < 0.05 ). The study highlights the importance of obtaining blood cultures in hospitalized children under five years old with diarrheal illness in the presence of either hospital-acquired infection or positive stool culture to have better outcome.